Serial Solutions-Workshop-Demo 21 Mei 2010. - Universiti Malaysia Sarawak, Centre for Academic Information Services (Centre for Academic Information Services, 2010)
Workshop Seral Solution ini diadakan pada 21 Mei 2010 di Maklmal Komputer tingkat 1 PKMA.